Diversity in grain physico-chemical characteristics of West African rice, including NERICA genotypes, as compared to cultivars from the United States of America - Traoré, K.; McClung, A.M.; Fjellstrom, R.; Futakuchi, K. (2011)
Landraces from West Africa (WA), NERICA progenies derived from crosses between Oryza sativa and Oryza glaberrima, and improved O. sativa lines from Africa Rice Center were introduced to the Beaumont Rice Research Center in Texas, United States of America (USA) (29o57’ N and 94o30’ W) for in-situ evaluation and characterization. Milled samples of rice produced in Côte d’Ivoire (CI) (7.5o N - 8.5o N and 4.5o W and 5.5o W) were also introduced for chemical analysis. RVA profiles showed that Jaya has unusually strong paste viscosity features. Apparent Amylose content varied from 15% for Khao Dawk Mali 105 originally from Thailand, to 26% for CG 14, an O. glaberrima type. WAB 56-104, an improved O. sativa variety from Africa Rice Center, had the longest cooking time of 24 minutes. Jaya can be compared to Dixiebelle, a USA variety grown commercially under contract for the canning and processing industries. Total milling yield varied from 78% for Gnanle Gnan-Man, a landrace from WA, to 70% for the USA check Saber. Sierra, a USA check, had the highest value of 2-AP (1258 ng/g), followed by Bakue Danane and Cocote, both from CI. Comparing WA samples grown in CI with those grown in Texas, cooking and pasting parameters were not generally strongly affected by the environment. The variable most affected by environment was the setback which predicts the hardness of cooked rice. Diverse sources for grain quality traits were found in WA germplasm for use in the USA.